Investigation of Single-Event-Transient Effects Induced by Heavy-Ion in All-Silicon DG-TFET - Ashish Maurya; Kalyan Koley; Jitendra Kumar; Pankaj Kumar (IEEE Access, 2022)
The heavy-ion analysis is a single-event-effect (SEE) that produces a single-event-transient (SET) pulse of current. In this work, the analysis was done to observe the maximum impact of heavy-ions on a calibrated double-gate tunnel field-effect transistor (DG-TFET) taken as a device under test (DUT). The impact of heavy-ions on DG-TFET is compared with the previous work done for different TFETs. The ions are directed to strike vertically at five different positions; source, source-body junction, body, drain-body junction, and the drain region of DG-TFET. The analysis is done by observing the heavy-ion generation rate, heavy-ion charge density, and transient current for the strike of the ion at different locations on the DUT and at different linear energy transfer (LET) values with the help of physics-based numerical simulation. In the study, a detailed analysis of the transient current due to a heavy-ion strike in the body region is reported, and this transient current is compared with the existing reported data for different FETs. Bipolar gain of the device is also observed for a heavy-ion strike in the body region, which is an important parameter for analyzing SEE. The findings in this study can give a new insight into SEE in TFET devices and can also provide guidelines for radiation-hardened applications for TFET-based circuits.